The efficacy of Poly-β-Hydroxy Butyrate (PHB)/biosurfactant derived from Staphylococcus hominis against White Spot Syndrome Virus (WSSV) in Penaeus monodon. Issue 71 (December 2017) - Monica, M.; Priyanka, T.; Akshaya, Murugesan; Rajeswari, V.; Sivakumar, Lingappa; Somasundaram, S.T.; Shenbhagarathai, R.
Abstract: White Spot Syndrome Virus (WSSV) is one of the most important causative agents of Penaeid shrimps diseases that incur heavy losses to the shrimp aquaculture. It has severe impact on the sustainability and the production of Penaeus monodon . Hence, the present study focussed on the investigation of Poly-β-hydroxybutyrate/biosurfactant as immunostimulants against WSSV infected shrimps. Infection of WSSV was periodically checked in all the experimental shrimps using PCR diagnostic kit. After ensuring all shrimps were free of viral infection, experiments were carried out to analyze the nonspecific immune responses (prophenol oxidase, nitro blue tetrazolium reduction assay and total haemocyte count) both in control and experimental group. Further, gills and muscles of Penaeus monodon were subjected to proteome analysis after treated it with PHB/biosurfactant independently in the concentration of 2% and 5% each. Increase in the level of haemocytes was observed in both PHB (26 ± 2 × 10⁴ cells)/biosurfactant (28 ± 2 × 10 4  cells) treated shrimps, when compared with control (17 ± 2 × 10⁴ cells). proPhenolOxidase (proPO) activity was also enhanced in treated groups compared to WSSV infected shrimps. Less production of superoxide anion was observed in control and treated groups. Differences in the protein expression was analyzed in muscle tissue of control, WSSV infected and PHB/biosurfactant treated shrimps. Our finding suggested that partial substitution of feed with 2% PHB and biosurfactant showed increased rate on the survival of WSSV infected P. monodon which might be due to either the over expression/down regulation of proteins that play a vital role in enhancing the immune system/the progression of the disease respectively. Highlights: PHB and biosurfactants from Staphylococcus hominis enhances the immunity against WSSV infection in Penaeus monodon. Immunological assays increased the survival rate of WSSV challenged Penaeus monodon treated with PHB/biosurfactant. 2-D gel electrophoretic pattern showed altered expression of proteins in PHB/biosurfactant treated shrimps.